Numerical Analysis of the Effects of the Geometric and Weight Parameters on the Exterior Ballistics of a Designed Counterprojectile - Marta CZYżEWSKA (Analiza numeryczna wpływu parametrów geometryczno -masowych projektowanego antypocisku na jegobalistykę zewnętrzną, 2017)
This paper presents a selection of deliverables of a research project intended to develop a technology demonstrator for an active protection system smart counterprojectile. Numerical simulations were completed to analyse the effects of geometry and weight of the counterprojectile warhead on the counterprojectile flight (motion) parameters. This paper investigates four variants of the counterprojectile warhead shape and three variants of the counterprojectile warhead weight. Given the investigated geometric and weight variants, the PRODAS software environment was used to develop geometric models of the counterprojectile warhead, followed by the determination of the model aerodynamic characteristics. The final deliverable of this work are the results of the numerical simulation of the counterprojectile motion along the initial flight path length. Given the required activation of the active protection system in direct proximity of the protected object, the analyses of counterprojectile motion parameters were restricted to a distance of ten-odd metres from the counterprojectile launching system.
Keywords: Balistyka zewnętrzna antypocisku